Mast cell marker gene signature: prognosis and immunotherapy response prediction in lung adenocarcinoma through integrated scRNA-seq and bulk RNA-seq - Zhang, Pengpeng; Liu, Jianlan; Pei, Shengbin; Wu, Dan; Xie, Jiaheng; Liu, Jinhui; Li, Jun (Frontiers in Immunology, 2023)
Background: Mast cells, comprising a crucial component of the tumor immune milieu, modulate neoplastic progression by secreting an array of pro- and antitumorigenic factors. Numerous extant studies have produced conflicting conclusions regarding the impact of mast cells on the prognosis of patients afflicted with lung adenocarcinoma (LUAD). Methods: Employing single-cell RNA sequencing (scRNA-seq) analysis, mast cell-specific marker genes in LUAD were ascertained. Subsequently, a mast cell-related genes (MRGs) signature was devised to stratify LUAD patients into high- and low-risk cohorts based on the median risk value. Further investigations were conducted to assess the influence of distinct risk categories on the tumor microenvironment. The prognostic import and capacity to prognosticate immunotherapy benefits of the MRGs signature were corroborated using four external cohorts. Ultimately, the functional roles of SYAP1 were validated through in vitro experimentation. Results: A prognostic MRGs signature, comprised of nine genes, was established following meticulous scrutiny of clinical attributes. The MRGs signature proved efficacious in distinguishing favorable survival outcomes within both training and validation cohorts. Moreover, we discerned individuals exhibiting robust immunotherapy response and favorable immune cell infiltration status. Cellular assays demonstrated that SYAP1 silencing substantially diminished LUAD cell proliferation, invasion, and migration capabilities, while augmenting LUAD cell apoptosis. Conclusion: Our MRGs signature offers valuable insights into the involvement of mast cells in determining the prognosis of LUAD and may prove instrumental as a navigational aid for immunotherapy selection, as well as a predictor of immunotherapy response in LUAD patients.